Kinetic properties of de-repressible alkaline phosphatase (EC 3.1.3.1) from Neurospora crassa - Palma, Mario Sergio [UNESP]; Han, S. W. [UNESP]; Rossi, A. (Springer Nature, 1991)
De-repressible alkaline phosphatase from N. crassa shows inhibition by PNP-P and a hyperbolic mixed-type inhibition by Pi. Both increasing concentrations of Pi and decreases in assay pH abolished inhibition by the substrate. Also, Pi promoted polymerization of the enzyme molecule, whose effect may account for the inhibitory behaviour shown by the enzyme in the presence of low Pi concentrations. © 1991 Rapid Communications of Oxford Ltd.